Fluxo de gases de efeito estufa em eolos do Pampa Gaúcho sob silvicultura - Godoi, Stefânia Guedes de (2012)
The soil use in the region of the Pampa Gaúcho has been modified by of forestation in soils previously used for agriculture or grazing. However, little is known about the impact of this change on greenhouse gases (GHG) fluxes in the soil in that region, mainly regarded to the methane (CH 4 ) and nitrous oxide (N 2 O). This study aimed to evaluate the effect of the conversion of native grassland to forestry, with Acacia mearnsii De Wild and Eucalyptus saligna, in the Pampa Gaúcho on the soil CH 4 and N 2 O fluxes, besides determining the soil variables that govern these fluxes. Two experiments were conducted for one year, in plantations of Acacia mearnsii De Wild evaluating four treatments: Acacia (AM), Acacia with manual litter removal (A-s), Acacia recently harvested (AH) and native grassland (NG); and Eucalyptus saligna evaluating five treatments: four–year Eucalyptus plantation (E4), four– year Eucalyptus plantation with manual litter removal (E4-l), two–year Eucalyptus plantation (E2), Native forest (NF) and Native grassland (NG), using the native grassland as reference treatment. The air samples were taken biweekly by the method of static chambers and gas concentrations were determined by gas chromatography. In each sampling event, we evaluated the soil moisture and mineral nitrogen content, deposition of litter and monitored the soil and chamber air temperature. The forestation with both eucalyptus and acacia did not alter significantly the soils fluxes of CH 4 and N 2 O in comparison to the native grassland adjacent to each forest. The N 2 O flux are generally low, with most values ranging from –5 to 30 μg N m -2 h -1 , probably favoured by the low rainfall and soil mineral nitrogen levels during the evaluated period. Similarly magnitude to the soil under native grassland, CH 4 oxidation predominated in forested soils in the period of the experiment. The soil with two-year old eucalyptus plantation tended to emit more N 2 O than the four-year plantation. The harvest of acacia increased the soil N 2 O emission, likely due to the larger availability of mineral N in the soil for the nitrification and denitrification processes. With respect to CH 4 , the largest emission coincided with periods of higher soil temperature, which is coherent herewith increased of the biological activity, especially in areas with less vegetation cover. The contents of total organic carbon (TOC) and total nitrogen (TN) in soils with eucalyptus and acacia were not significantly different from those observed in native grassland soil for most layers. The low CH 4 and N 2 O emissions from forestry added to the carbon sequestration in the plant biomass and wood products suggests that the change of land use for forestation is an effective option for mitigating the GHG emissions and for increasing the carbon sequestration in areas such as the Pampa Gaúcho.